Optimasi Aplikasi Tepung Asap dari Tanaman Bambu Terhadap Pengawetan Siomay - Utomo , Hanif Aulia ; Lestari , Ludianarti Rahayu ; Abrina Anggraini , Sinar Perbawani (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Siomay is a product made from fresh mackerel fish made by steaming. However, dumplings have a relatively short shelf life. Syrup has a relatively short shelf life at room temperature. Generally the non-vacuum dumplings save only lasts 2 days. The need for natural preservatives is safe to consume to increase the shelf life of the dumplings. Generally, foods containing protein elements when decaying the levels of protein contained in food will decrease. The technology commonly used is liquid smoke. But the problem In addition to the content of phenolic compounds liquid smoke is easily damaged (oxidation) during storage. Handling of liquid smoke requires the development of technology by converting liquid smoke into flour or powder, which is through nanoencapsulation technology so that it will increase the shelf life of food products. Based on the results of the research that has been done is the quality of the smoke flour contains a percentage of phenol content of 3.15%, while in the dumplings dumplings which have added smoke flour 5% the percentage of phenol content is 1.80%. In the dumplings which are added with smoke flour 10% the percentage of phenol content is 2.24%. Three-day observations carried out on decreasing levels of siomay protein added with 5% smoked flour showed a decrease in protein content of 0.98%, while those in smoke dumplings added by 10% decreased the protein content by 0.74%. From the observation of siomay given with smoked flour with non-smoked flour showed that simay dough can last more than three days. Optimization of adding smoked flour which is good for maintaining protein content is 10%.